2022
DOI: 10.1021/acs.energyfuels.2c01996
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and Wetting Properties in Shale/Methane/Water and Shale/Methane/Surfactant Systems at Geological Conditions

Abstract: Understanding surface properties such as wettability and CH4/shale interfacial tension (IFT) is essential to decipher CH4 productivity and hydrocarbon-in-place estimates. However, these factors are poorly understood due to lack of data despite their importance. We thus measured the equilibrium contact angle (θe), reflecting the degree of wetting for shale/CH4/water systems, and determined the governing interfacial tensions. In particular, water/CH4, water/shale, and CH4/shale IFTs are determined at pressures 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Previous studies of microscopic water distribution in minerals [17,18] and organic matter [15,19] have demonstrated the strong hydrophilicity of clay minerals and the mixed wettability of organic matter. Extensive experiments [20,21] and molecular simulations [18,22] have shown that water can significantly reduce the methane adsorption capacity in shale pores, with mechanisms including adsorption site capture, pore space occupation, and methane partial pressure reduction [15,19,23]. Previous studies of methane adsorption in water-bearing shale pores have mainly focused on the influence of water on methane adsorption and its mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of microscopic water distribution in minerals [17,18] and organic matter [15,19] have demonstrated the strong hydrophilicity of clay minerals and the mixed wettability of organic matter. Extensive experiments [20,21] and molecular simulations [18,22] have shown that water can significantly reduce the methane adsorption capacity in shale pores, with mechanisms including adsorption site capture, pore space occupation, and methane partial pressure reduction [15,19,23]. Previous studies of methane adsorption in water-bearing shale pores have mainly focused on the influence of water on methane adsorption and its mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase in energy demand, along with the depletion of conventional wells, has prompted considerable interest in exploring and developing unconventional oil and gas reservoirs . Unconventional hydrocarbon reservoirs, such as shales, possess low porosity, ultralow reservoir permeability, poor connectivity, and non-Darcy flow. The current development of unconventional oil and gas reservoirs relies significantly on horizontal drilling processes in conjunction with hydraulic fracturing. The recovery of hydrocarbons from shale and other unconventional formations has been justified to be economically feasible due to such stimulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…There are six original contributions and two reviews on this topic. Abdulelah et al 15 measured the interfacial and wetting properties in shale/methane/water and shale/methane/surfactant [cetyltrimethylammonium bromide (CTAB)] systems at geological conditions. They also measured excess CH 4 adsorption on the shale surfaces before/after treating with CTAB.…”
mentioning
confidence: 99%